2010
DOI: 10.1007/s11581-010-0426-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of the microstructural and photoluminescence properties of Li-doped ZnO thin films prepared by spray pyrolysis

Abstract: Lithium-doped zinc oxide films were synthesized by spray pyrolysis technique, and their structural and optical properties were characterized by X-ray diffraction, transmission electron microscope, atomic force microscope, and photoluminescence spectroscopy. The effect of doping on the photoluminescence properties was investigated at room temperature (300 K). Polycrystalline nature of the films was confirmed from X-ray diffraction and electron microscopic studies. A two-dimensional fringe moiré pattern with spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…It is reported that these peaks at positions 388.6 and 381.7 nm are originated from bound excitonic recombination and free excitonic recombination, respectively [36][37][38]. Also, it is suggested that the broad UV emission peaks are related to plenty of dislocations and intrinsic and extrinsic defects like ionized donor bound exciton complex that are formed during the sputtering [30]. Although the XRD results showed higher and narrower peak intensity for the film deposited on Al 2 O 3 substrate, the PL spectra indicated that the highest UV intensity is observed at the sputtered film on Si substrate, which has the smallest textured grains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that these peaks at positions 388.6 and 381.7 nm are originated from bound excitonic recombination and free excitonic recombination, respectively [36][37][38]. Also, it is suggested that the broad UV emission peaks are related to plenty of dislocations and intrinsic and extrinsic defects like ionized donor bound exciton complex that are formed during the sputtering [30]. Although the XRD results showed higher and narrower peak intensity for the film deposited on Al 2 O 3 substrate, the PL spectra indicated that the highest UV intensity is observed at the sputtered film on Si substrate, which has the smallest textured grains.…”
Section: Resultsmentioning
confidence: 99%
“…Calculations by Zhang et al [29] showed that the (V O ) and (Zn i ) native defects have a low formation enthalpy. In most cases, the photoluminescence (PL) spectra of pure ZnO consist of two principal emission peaks, one in near UV region (around 3.3 eV), corresponding with the near band edge emission of crystalline ZnO, and the other in the bluegreen region (around 2.5 eV), which is ascribed to the various crystalline defects like doubly ionized zinc vacancy, oxygen vacancy, antisite oxygen, zinc interstitial, or with extrinsic dopants like Al [30,31]. So the photoluminescent centers are associated with crystalline structure and native defects of ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…The required amount of cupric acetate solution was added to aqueous zinc acetate solution (0.1 M) to obtain a copper concentration of 5 wt.% in the ZnO thin films. The experimental procedure remained same as described elsewhere [19].…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that Cu atoms can replace Zn atoms either substitutional (Cu Zn ) or interstitial (Cu i ) in the ZnO lattice creating structural deformations, thereby affecting the electrical, chemical, structural, and optical properties of ZnO significantly. In our earlier studies, we have reported the dependence of structural and optical properties of ZnO on various defects and external impurities like Li and Al [19,20]. For nitrogen doping, atomic nitrogen from sources like NH 3 with post deposition annealing [21] or through a co-doping method (Ga/Al) [22][23][24] is preferred by all researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Another study about ZnO:Li films was reported [124] for thin films deposited on borosilicate glass substrates; the deposition temperature was kept at 250 °C. The spraying solution was 0.2 M zinc acetate in a mixture of equal proportion of isopropyl alcohol and deionized water.…”
Section: Luminescent Materialsmentioning
confidence: 99%